The seduction - Briscoe, Joanna (Novelist) (Bloomsbury Publishing, 2020)
"Beth Penn lives a peaceful life with her partner Sol and their daughter Fern. But Beth is troubled by increasing unease. She cannot shake her uncertainty over her mother, who disappeared when Beth was a child, and she has a sense that her daughter is keeping secrets from her. So she goes to therapy. Dr. Tamara Bywater is there to help her patients. But what if the very person who is meant to be the solution becomes the most dangerous problem of all? And why is what's bad for us so enticing?"--